Prevention and Management of Infectious Complications of Retrograde Intrarenal Surgery - Khusid, Johnathan A.; Hordines, John C.; Sadiq, Areeba S.; Atallah, William M.; Gupta, Mantu (Frontiers in Surgery, 2021)
Kidney stone disease (KSD) is a commonly encountered ailment in urologic practice. Urinary tract infection (UTI) is commonly associated with KSD, both as an etiology (e.g., struvite and carbonate apatite stones), and as a complication (i.e., obstructive pyelonephritis and post-operative UTI). Indeed, a significant portion of the economic burden of KSD is skewed towards stones associated with infection. UTI is the most common post-operative complication related to stone intervention with progression to urosepsis as a rare but serious consequence. Risk for infection is influenced by a variety of factors including co-morbid conditions, anatomic abnormalities, prior surgical procedures, and local anti-microbial susceptibility. Understanding these risks and the proper steps to mitigate them is an essential component in reducing post-operative morbidity and mortality. Retrograde intrarenal surgery is routinely used for the treatment of KSD. The objective of this review article is to examine the current literature and guidelines for the prevention and management of stone-related infectious complications associated with retrograde intrarenal surgery. Special attention will be given to the incidence, etiology, and antibiotic prophylaxis choice in the management of stone-related infections. Intraoperative risk mitigation techniques will be discussed in conjunction with the management of post-operative infections. Antibiotic stewardship and the potential benefits of reduced empiric antibiotic treatment will also be discussed.